Die Aufklärung retten: postkoloniale Interventionen - Dhawan, Nikita (2016)
Abstract: Rezension zu: 1) Allen, Amy, 2016: The End of Progress: Decolonizing the Normative Foundations of Critical Theory. New York. 2) Flikschuh, Katrin; Ypi, Lea, 2014 (Eds.): Kant and Colonialism: Historical and Critical Perspectives. Oxford